Grapevine red blotch virus (GRBV) in a historical germplasm collection in south-eastern Australia - Kamalpreet Kaur; Amy Rinaldo; David Lovelock; Monica Kehoe; Tonny Kinene; Arryn Clarke; Ian Dry; Brendan Rodoni; Fiona Constable (OENO One)
The first detection of grapevine red blotch virus (syn. GRBV; species Grablovirus vitis, genus Grablovirus, family Geminiviridae) in Australia was initially reported in several grapevine varieties in Western Australia in 2022, but its impact and spread in the country is still currently unknown. In this study, GRBV was detected in 14 locally selected and imported wine, table and dried grapes varieties from a historical germplasm collection in Victoria (n = 12) and in germplasms in South Australia (n = 2), using a combination of a nested endpoint polymerase chain reaction (PCR) assay and tiled amplicon genome sequencing. Phylogenetic and median-joining network analyses indicated that there may have been at least three separate introductions of GRBV into the historical germplasm collection. The phylogenetic, sequence identity, median-joining network, and single nucleotide polymorphism analyses indicate a close relationship between the South Australian, Western Australian and most Victorian GRBV isolates, which appear to have emerged from an introduction of infected Vitis vinifera cv. Perle de Csaba in the 1960s. Spatial analyses and the known history of the 14 infected Victorian and South Australian varieties, also provide evidence of GRBV spread via vegetative propagation of Perle de Csaba from the historical collection to South Australia and Western Australia. The analyses also indicated that a very slow and inefficient spread of GRBV between vines in the same vineyard has also possibly occurred via an unknown vector. Seasonal testing of selected varieties from the Victorian collection suggests winter as the optimal time for GRBV testing under environmental conditions in north-west Victoria.